2017
DOI: 10.3390/coatings7120216
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Power Pulse Parameters on the Microstructure and Properties of the AlCrN Coatings by a Modulated Pulsed Power Magnetron Sputtering

Abstract: Abstract:In this study, AlCrN coatings were deposited using modulated pulsed power magnetron sputtering (MPPMS) with different power pulse parameters by varying modulated pulsed power (MPP) charge voltages (350 to 550 V). The influence of power pulse parameters on the microstructure, mechanical properties and thermal stability of the coatings was investigated. The results indicated that all the AlCrN coatings exhibited a dense columnar microstructure. Higher charge voltage could facilitate a denser coating mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…At higher ion source powers, the gas ionization rate increased; after a series of ion collisions and energy transfer, more ions with high energy were delivered into the growing coating surfaces, which promoted grain growth and nucleation in the coatings. Additionally, the thermal effect induced by the strong ion bombardment also promoted slight grain growth [27]. Figure 6a displays the XRD pattern of the AlTiVCuN/CrN coatings at various ion source powers.…”
Section: Microstructurementioning
confidence: 99%
“…At higher ion source powers, the gas ionization rate increased; after a series of ion collisions and energy transfer, more ions with high energy were delivered into the growing coating surfaces, which promoted grain growth and nucleation in the coatings. Additionally, the thermal effect induced by the strong ion bombardment also promoted slight grain growth [27]. Figure 6a displays the XRD pattern of the AlTiVCuN/CrN coatings at various ion source powers.…”
Section: Microstructurementioning
confidence: 99%
“…As an important pulse parameter, the charge voltage also exhibited a significant effect on the microstructure evolution and mechanical properties. For example, Zheng et al [27] deposited the AlCrN coatings by MPPMS technique at various charge voltages, and found that higher charge voltage corresponded to a higher plasma density and stronger ionization, resulting in much denser microstructure, which increased the coating hardness.…”
Section: Introductionmentioning
confidence: 99%
“…Thickness dependence, which is mainly due to deposition time or power variations of the magnetic hysteresis observed in NiFeAg heterogeneous alloy films at ambient temperature onto glass substrates [ 39 ]. Higher charge voltage could expedite AlCrN coatings having a compact columnar microstructure by means of modulated pulsed power magnetron sputtering (MPPMS), with altered power pulse parameters [ 40 ]. In principle, if the particle size dispersal rests constant with thickness, the GMR in heterogeneous alloys would not be affected.…”
Section: Introductionmentioning
confidence: 99%